Classification and Association Analysis of Gerbera (Gerbera hybrida) Flower Color Traits - Zhou, Yiwei; Yin, Mao; Abbas, Farhat; Sun, Yue; Gao, Ting; Yan, Fulong; Li, Xinyue; Yu, Yunyi; Yue, Yuechong; Yu, Rangcai; Fan, Yanping (Frontiers in Plant Science, 2022)
Floral color plays a crucial role in plant life such as plant-pollinator interactions and modifying the abiotic environment of reproductive structures. In the current study, 123 gerbera accessions were divided into six color groups (white, yellow, orange, pink, red, and purple), based on Royal Horticultural Society Color Chart calibration and colorimeter measurement. Partial least squares discriminant analysis showed that the white group was mainly affected by L* value, a* value, C value, and total anthocyanin contents, while the yellow group was positively correlated with L* value, b* value, and total anthocyanin contents. Similarly, the orange group was mainly affected by b* value and total carotenoid contents, whereas the pink group was positively correlated with L* and h values. Furthermore, the red group was affected by L* value, a* value, C value, and total anthocyanin contents, whilst the purple group was mainly distributed by L* value, a* value, b* value, and total anthocyanin contents. Based on ‘Jin Xiang’ transcriptome data, 14,106 expressed sequence tag (EST)-SSR markers were identified and 48 pairs of primers (19 newly developed primers) were screened. Population genetic structure, neighbor-joining clustering, and principal coordinate analysis showed that 123 gerbera accessions could be divided into two groups. EST-SSR-based association analysis showed that 1, 1, 2, 1, 1, 2, and 1 significant loci were related to L*, a*, b*, C, and h, total carotenoid, and total anthocyanin contents, respectively. These results provide an important reference for flower color classification and genetic improvement of gerbera.